Complicated Spontaneous Coronary Artery Dissection (SCAD) Culminating in Aneurysm Formation: Coronary Artery Bypass Graft Surgery Is Preferable Over Percutaneous Coronary Intervention in Peripartum SCAD - Moghadam, Reihaneh (Cureus, 2021)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS), most frequently occurring in young females of reproductive age, and has a high mortality rate. Currently, no guidelines are available to direct treatment. We report a case of a 29-year-old female with complications of SCAD treated with coronary artery bypass graft (CABG), resulting in a better outcome as compared to that of percutaneous coronary intervention (PCI). Our patient presented with class IV angina one-year post-PCI following postpartum SCAD. Left heart catheterization (LHC) reported SCAD involving the ostium of the left circumﬂex (LCX) and then cutting off the left marginal artery, which was followed by a 2.5 x 28 mm Synergy drug-eluting stent (Boston Scientific, Marlborough, MA) x1 in the lateral branch of the bifurcating marginal system with good coronary stent results. Repeat LHC one-year after the SCAD was signiﬁcant for a large aneurysm in the distal left main coronary artery (LCA) extending into the LCX with evidence of a residual large false lumen (0.41 sq cm), as compared to the narrow segment of the true lumen (0.15 sq cm). Compared to the distal LCA area (0.49 sq cm), the true lumen of the LCA had severe stenosis. The patient underwent three-vessel CABG (left internal mammary artery (LIMA)-> left anterior descending artery (LAD), right internal mammary artery (RIMA)->first obtuse marginal (OM1), saphenous vein graft (SVG)->second obtuse marginal (OM2)) with sternal plating. The patient was doing well three months post-CABG with complete resolution of the pain, which was unattainable by PCI. Our report suggests that CABG may be preferable over PCI in the peripartum SCAD to avoid complications or sudden cardiac death from the extension of the dissection and aneurysm formation.